CARe in an INterGenerational context (CARING) - Tiziana Nazio (PRj - The Project Repository Journal, 2019)
The project analysed the role played by early life course family formation trajectories (at 16-46 years) in shaping emotional support networks and care provision to old age persons in Europe (50+ years) for the birth cohorts 1927-66. Sequence and cluster analyses, together with multivariate models, explored the size of emotional support networks for the elderly, and the likelihood to report help received or given. It also explored the overlap of the two types of care, i.e. how the emotional support network contributed to also offering practical help or personal care. Analyses were based on secondary data analysis of retrospectively collected information from wave 3 and 7 and cross-sectional data from wave 4, 6 and 7 of the data from the Survey of Health, Ageing and Retirement in Europe (SHARE) for five countries: Italy, East and West Germany, France, Denmark and Czech Republic.
Keywords: 330